Adaptive Reuse of Russian-Influenced Religious Architecture in Harbin: Architectural Identity and Heritage Tourism - Se Yan; Shiran Geng; Hing-Wah Chau; Tian Wang; Elmira Jamei; Zora Vrcelj (Heritage)
Adaptive reuse is a widely employed strategy for heritage conservation and management, especially within the context of heritage tourism. However, its application to religious architecture presents unique challenges that have not been thoroughly explored. In Harbin, a city in northeastern China known for its Russian-influenced heritage, many abandoned religious-affiliated buildings have been repurposed for other functions. Such transformations raise concerns about how the architectural features and the functionalities of these buildings have been preserved and reused. This study investigates the adaptive reuse strategies applied to Russian-influenced religious buildings in Harbin, focusing on how these strategies impact architectural preservation and sustainable heritage tourism development. It begins by documenting the distinctive architectural styles of Russian-influenced religious buildings in Harbin, followed by a detailed analysis of the selected case studies. The study evaluates the current conditions and uses of these buildings, identifying both the opportunities and constraints of adaptive reuse. The findings reveal a balance between preserving external architectural features and adapting interior spaces to accommodate various functions, particularly in sacred-to-secular transformations. This study highlights the complexities of reconciling historical authenticity with economic viability by comparing sacred-to-sacred adaptations—which retain community relevance—with sacred-to-secular conversions—which prioritise cultural utility. It further examines how historical events and the Western and Chinese conservation dichotomy shape current adaptive reuse practices and preservation priorities in Harbin, offering broader insights into balancing cultural symbolism and functionality in heritage tourism. The findings provide valuable recommendations for policymakers to optimise adaptive reuse practices in religious heritage buildings, ensuring the preservation of architectural identities while supporting sustainable heritage tourism.